Summer phytoplankton assemblages and carbon biomass in the northern south China sea. (26th December 2020) - Gui, Jiang; Wei, Yuqiu; Sun, Jun; Le, Fengfeng; Cai, Yuming; Ning, Xiuren
Abstract: Phytoplankton assemblage composition, abundance, carbon biomass and distribution were studied in summer 2004 in the northern South China Sea (NSCS; 18°-22°N, 110°-117°E). This is the first report of natural phytoplankton assemblages which were analyzed by Utermöhl method and their biovolume conversion carbon biomass in the NSCS. A taxa of phytoplankton was identified, which belong to 4 classes and 76 genera, and mainly composed of Bacillariophyceae. Most of them belong to nanophytoplankton (Equivalent Sphere Diameter is 10–15 μm). Associated phytoplankton, with a share of 3% UPA (Utermöhl phytoplankton assemblage cell abundance), primarily consisted of Dinophyceae. Chrysophyceae and Cyanophyceae occurred in appreciable amounts only at upper layers waters in the NSCS. Combined the UPC (Utermöhl phytoplankton carbon) with PPC (picophytoplankton carbon) into the BPC (bulk phytoplankton carbon biomass), it ranged from 0.117 to 1467.172 μg C L −1, its average was 54.848 ± 197.578 μg C L −1 . The ratios of PPC contribution to BPC ranged from 0.001% to 6.567%, its average was 0.667 ± 1.215%. This indicates that picophytoplankton contribution to phytoplankton carbon pool is much low than that of chlorophyll a partitioning. Two carbon biomass provinces, one was higher biomass province along continental surface and bottom layers, and the other one was lower biomass province in open sea waters, were clearly discerned along the isoline of 20 μg C L −1 . The calculated budget amount BPC pool in the NSCS was 1.21 × 10 4 tC. The calculated Carbon: Chlorophyll a ratio (C: Chl a ) in study area ranged from 0.21 to 217.648, its average was 37.31 ± 46.53. Several typical phytoplankton assemblages can be discerned based on Shannon-Wiener diversity index, Pielou's evenness and C: Chl a . Examination of phytoplankton abundances, biomass and environmental factors by multivariate techniques PCA (Principal Component Analysis) suggests BPC distribution in the NSCS was mainly controlled by salinity at Section along PRE (Pearl River estuary) to Dongsha Islands, and nitrate concentration at Section along the Yangjiang to Zhongsha Islands. The keystone phytoplankton species in the NSCS were mainly composed of large or chain form Bacillariophyceae, such as Pseudo - nitzschia delicatissima, Chaetoceros spp. and Asterionellopsis glacialis, and some Dinophyceae also take an important role in the NSCS, such as Gyrodinium spirale and Prorocentrum dentatum . In addition, the features of phytoplankton distribution were according to functional morphology. Highlights: First use of Utermöhl method in China.